Disentangling the effects of high permittivity materials on signal optimization and sample noise reduction via ideal current patterns. Issue 4 (13th November 2018) - Vaidya, Manushka V.; Sodickson, Daniel K.; Collins, Christopher M.; Lattanzi, Riccardo
Abstract : Purpose: To investigate how high‐permittivity materials (HPMs) can improve SNR when placed between MR detectors and the imaged body. Methods: We used a simulation framework based on dyadic Green's functions to calculate the electromagnetic field inside a uniform dielectric sphere at 7 Tesla, with and without a surrounding layer of HPM. SNR‐optimizing (ideal) current patterns were expressed as the sum of signal‐optimizing (signal‐only) current patterns and dark mode current patterns that minimize sample noise while contributing nothing to signal. We investigated how HPM affects the shape and amplitude of these current patterns, sample noise, and array SNR. Results: Ideal and signal‐only current patterns were identical for a central voxel. HPMs introduced a phase shift into these patterns, compensating for signal propagation delay in the HPMs. For an intermediate location within the sphere, dark mode current patterns were present and illustrated the mechanisms by which HPMs can reduce sample noise. High‐amplitude signal‐only current patterns were observed for HPM configurations that shield the electromagnetic field from the sample. For coil arrays, these configurations corresponded to poor SNR in deep regions but resulted in large SNR gains near the surface due to enhanced fields in the vicinity of the HPM. For very high relative permittivity values, HPM thicknesses corresponding to even multiples of λ/4 resulted in coil SNR gains throughout the sample. Conclusion: HPMs affect both signal sensitivity and sample noise. Lower amplitude signal‐only optimal currents corresponded to higher array SNR performance and could guide the design of coils integrated with HPM.